Effect of Harvest and Drying on Composition of Volatile Profile of Elderflowers (Sambucus nigra) from Wild - Bajer, Tomáš; Bajerová, Petra; Ventura, Karel (My University, 2017)
Volatile compounds emitted by elderflowers (Sambucus nigra L.) at various stages (blooming on the bush, and at different stages after harvesting) were analyzed to investigate changes in the composition of volatile profiles induced by two drying procedures. Solid-phase microextraction and simultaneous distillation-solvent extraction were used for concentration of volatiles. Analyses of extracts were performed using gas chromatography coupled with a mass spectrometer or a flame ionization detector. On-site field sampling of volatiles followed-up by chromatographic analysis provided interesting information, including insect pheromones from 55 % to 79 % of the total peak area in the GC/MS chromatograms. Composition of aroma compounds of harvested elderflowers was strongly influenced by the type of drying procedure, where the content of some volatiles decreased and some substances even occur due to ongoing physicochemical processes. Changes in volatile profile caused by harvesting were also observed.
Vliv sklizně a sušení na složení aromaprofilu květů černého bezu (Sambucus nigra)
Keywords: Elderflowers; SPME; SDE; Essential oil; GC/MS; Volatiles; Květy černého bezu; SPME; SDE; Esenciální olej; GC/MS; Těkavé sloučeniny